PROSES AKULTURASI KERUANGAN KOMUNITAS MUSLIM KAMPUNG JAWA DI PERKOTAAN TABANAN BALI - Agam Marsoyo; Rahma Rizqyani (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
The traditional rules of Bali regulate the use of space as a manifestation of the rules of palemahan in the Tri Hita Karana concept. The arrival of Moslem migrants to Tabana urban area forms the Moslem community of Kampung Jawa which is the largest Moslem community in the Tabanan urban area and still exists today. The high intensity of interaction between Moslems and Hindus has resulted in spatial acculturation related to the rules of palemahan. This research aims to find out the process of spatial acculturation of the Moslem community in urban Tabanan Bali. The method used was a case study method with the Kampung Jawa area as a case unit. Data collection of case evidence was obtained through observation and in-depth interviews to the informant who are considered to have knowledge of the variety and spatial acculturation processes that occur and supported by other secondary data. This study found a different process and time of formation in each type of spatial acculturation that occurred. Spatial acculturation of the Moslem community of the Kampung Jawa in Tabanan urban takes several stages of the process, namely: (1) social interaction, (2) Moslem understanding of Hinduism, (3) Moslem adaptation, (4) Hindus understanding of Moslems, (5) acculturation, and (6) expansion of space, actors, and type of spatial acculturations.